Interpretation of Acousting Sounding Records with Meterological Parameters and Ventilation Coefficient Over Delhi - Singh, P.; Soni, K.; S. Nair, A.; Kumar, N.; Sharma, R. (Journal of Scientific Research, 2022)
Atmospheric Boundary Layer (ABL) height is an important parameter in defining the Ventilation Coefficient (VC) of any area. In this work, SODAR (Sound Detection and Ranging) observed data of different echograms for the year 2020 has been used for structure identification. The interpretation of ecograms is often not straight-forward. In this paper, an interpretation of different echograms along with meteorological parameters over Delhi is described. The ecogram structures were interpreted along with VC analysis. It is observed from the structures that during foggy days, VC values vary from day to day in the winter, with daily maximum values occurring between 13:00 and 15:00 h. The daytime values varied significantly from sunrise to sunset, while the night-time values remained relatively stable (200 m2/s). However, due to fog diurnal variation from 16:00 h to 11:00 h, that is from evening to all night and then the next morning until 12:00 h, the atmospheric condition remained stable. At maximal wind speeds, a maximum VC of 1600 m2/s (at 12:00 h) was observed during extended fumigation. With minimal wind speeds and ABL height, a minimum VC of 100 m2/s (at 20:00 h) was observed. However, both VCs were smaller than the optimal VC for 6000 m2/s safe dispersion.